Inhibitory Effects of Chrysanthemum boreale Essential Oil on Biofilm Formation and Virulence Factor Expression of Streptococcus mutans. (11th February 2015) - Kim, Beom-Su; Park, Sun-Ju; Kim, Myung-Kon; Kim, Young-Hoi; Lee, Sang-Bong; Lee, Kwang-Hee; Choi, Na-Young; Lee, Young-Rae; Lee, Young-Eun; You, Yong-Ouk
Abstract : The aim of the study was to evaluate the antibacterial activity of essential oil extracted from Chrysanthemum boreale ( C. boreale ) on Streptococcus mutans ( S. mutans ). To investigate anticariogenic properties, and bacterial growth, acid production, biofilm formation, bacterial adherence of S. mutans were evaluated. Then gene expression of several virulence factors was also evaluated. C. boreale essential oil exhibited significant inhibition of bacterial growth, adherence capacity, and acid production of S. mutans at concentrations 0.1–0.5 mg/mL and 0.25–0.5 mg/mL, respectively. The safranin staining and scanning electron microscopy results showed that the biofilm formation was also inhibited. The result of live/dead staining showed the bactericidal effect. Furthermore, real-time PCR analysis showed that the gene expression of some virulence factors such as gtf B, gtf C, gtf D, gbp B, spa P, brp A, rel A, and vic R of S. mutans was significantly decreased in a dose dependent manner. In GC and GC-MS analysis, seventy-two compounds were identified in the oil, representing 85.42% of the total oil. The major components were camphor (20.89%), β -caryophyllene (5.71%), α -thujone (5.46%), piperitone (5.27%), epi -sesquiphellandrene (5.16%), α -pinene (4.97%), 1, 8-cineole (4.52%), β -pinene (4.45%), and camphene (4.19%). These results suggest that C. boreale essential oil may inhibit growth, adhesion, acid tolerance, and biofilm formation of S. mutans through the partial inhibition of several of these virulence factors.